2021
DOI: 10.1001/jamanetworkopen.2020.36695
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin, Body Mass Index, and Age as Risk Factors for Paclitaxel- and Oxaliplatin-Induced Peripheral Neuropathy

Abstract: IMPORTANCE Chemotherapy-induced peripheral neuropathy (CIPN) is a debilitating adverse effect of neurotoxic cancer treatments including taxanes and platinum agents. Limited knowledge exists of potential prechemotherapy factors associated with CIPN development. OBJECTIVE To identify the association of pretreatment blood-based and clinical factors with CIPN persistence in patients who received paclitaxel or oxaliplatin. DESIGN, SETTING, AND PARTICIPANTS This cohort study assessed pretreatment blood-based clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 64 publications
5
51
3
Order By: Relevance
“…Mizrahi et al carried out a large cross-sectional study including 105 patients treated with OXA. The results showed a correlation between reduced pretreatment levels of hemoglobin, detected in 24.5% of the cohort, with a greater severity of neuropathy [ 14 ]. In addition, previous studies on patients receiving OXA concluded similar results [ 15 , 19 , 22 , 27 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%
See 4 more Smart Citations
“…Mizrahi et al carried out a large cross-sectional study including 105 patients treated with OXA. The results showed a correlation between reduced pretreatment levels of hemoglobin, detected in 24.5% of the cohort, with a greater severity of neuropathy [ 14 ]. In addition, previous studies on patients receiving OXA concluded similar results [ 15 , 19 , 22 , 27 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Among pretreatment metabolic and nutritional blood-based biomarkers, there are conflicting results. Such as higher albumin level [ 14 ] as hypoalbuminemia [ 15 , 19 ] have been associated with the risk of developing OXAIPN. Despite higher rates of neurotoxicity were described in patients with low levels of magnesium, the lack of evidence in this line [ 14 ] would support the known inefficacy of calcium-magnesium supplementation during OXA treatment as a neuroprotective approach [ 9 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations